Development and implementation of a time- and computationally-efficient methodology for reconstructing real-world crashes using finite element modeling to improve crash injury research investigations. Issue 12 (30th August 2022) - Costa, Casey; Gaewsky, James P.; Stitzel, Joel D.; Gayzik, F. Scott; Hsu, Fang-Chi; Martin, R. Shayn; Miller, Anna N.; Weaver, Ashley A.
Abstract: Eleven Crash Injury Research and Engineering Network (CIREN) frontal crashes were reconstructed using a novel, time-efficient methodology involving a simplified vehicle model. Kinematic accuracy was assessed using novel kinematic scores between 0-1 and chest injury was assessed using literature-defined injury metric time histories. The average kinematic score across all simulations was 0.87, indicating good kinematic accuracy. Time histories for chest compression, rib strain, shoulder belt force, and steering column force discerned the most causative components of chest injury in all cases. Abbreviated Injury Scale (AIS) 2+ and AIS 3+ chest injury risk functions using belt force identified chest injury with 81.8% success.